The Acquired Vulnerability Caused by CDK4/6 Inhibition Promotes Drug Synergism Between Oxaliplatin and Palbociclib in Cholangiocarcinoma - Suppramote, Orawan; Prasopporn, Sunisa; Aroonpruksakul, Satinee; Ponvilawan, Ben; Makjaroen, Jiradej; Suntiparpluacha, Monthira; Korphaisarn, Krittiya; Charngkaew, Komgrid; Chanwat, Rawisak; Pisitkun, Trairak; Okada, Seiji; Sampattavanich, Somponnat; et al. (Frontiers in Oncology, 2022)
Cholangiocarcinoma (CCA) is one of the most difficult to treat cancers, and its nature of being largely refractory to most, if not all, current treatments results in generally poor prognosis and high mortality. Efficacious alternative therapies that can be used ubiquitously are urgently needed. Using acquired vulnerability screening, we observed that CCA cells that reprofile and proliferate under CDK4/6 inhibition became vulnerable to ribosomal biogenesis stress and hypersensitive to the anti-ribosome chemotherapy oxaliplatin. CCA cells overexpress the oncogenic ribosomal protein RPL29 under CDK4/6 inhibition in a manner that correlated with CDK4/6 inhibitor resistance. Depletion of RPL29 by small interfering RNAs (siRNAs) restored the sensitivity of CCA cells to CDK4/6 inhibition. Oxaliplatin treatment suppressed the RPL29 expression in the CDK4/6 inhibitor treated CCA cells and triggered RPL5/11-MDM2-dependent p53 activation and cancer apoptosis. In addition, we found that combination treatment with oxaliplatin and the CDK4/6 inhibitor palbociclib synergistically inhibited both parental and CDK4/6 inhibitor-resistant CCA, and prevented the emergence of CDK4/6 and oxaliplatin-resistant CCA. This drug combination also exerted suppressive and apoptosis effects on CCA in the in vitro 3-dimensional culture, patient-derived organoid, and in vivo xenograft CCA models. These results suggest the combination of the CDK4/6 inhibitor palbociclib and the anti-ribosome drug oxaliplatin as a potentially promising treatment for cholangiocarcinoma.